2021
DOI: 10.1016/j.jtcme.2021.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Egyptian Olea europaea leaves bioactive extract: Antibacterial and wound healing activity in normal and diabetic rats

Abstract: Background and aim In vitro activity evaluation of Egyptian Olea europaea leaves extracts, and in vivo healing activity assessment of the newly prepared ointment of Olea europaea leaves extracts mingled with Shea butter. Experimental procedure Different extraction methods and solvents were used to extract Egyptian Olea europaea bioactive agent(s). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 30 publications
1
13
2
Order By: Relevance
“…This data appears in contrast to other literature studies in which OLE was found to be active both as an antibacterial and an accelerator of wound healing. The concentrations tested were higher than that applied in the present work [37]. In another work, it was shown in vivo that wound healing was promoted by olive leaf extracts and that this effect was greater the greater was the scavenging ability of the extract [38].…”
Section: In Vitro Scratch Wound Healing Assaycontrasting
confidence: 56%
“…This data appears in contrast to other literature studies in which OLE was found to be active both as an antibacterial and an accelerator of wound healing. The concentrations tested were higher than that applied in the present work [37]. In another work, it was shown in vivo that wound healing was promoted by olive leaf extracts and that this effect was greater the greater was the scavenging ability of the extract [38].…”
Section: In Vitro Scratch Wound Healing Assaycontrasting
confidence: 56%
“…Anti-staphylococcal activity is characteristic for all three extracts. Compared to some published studies, the MIC value of complex exceeds that of individual extracts, e.g., 2.68 mg/mL of olive leaf extract reported by Pereira et al and 2.5 mg/mL by Karygianni et al, compared to 0.78 mg/mL in our study [ 21 , 23 ]; some other authors reported higher activity, e.g., a MIC value of 15.6 μg/mL of olive extract against MRSA [ 82 ], or similar results, such as MIC values for propolis in the range of 0.39–0.78 mg/mL [ 41 ]. In general, data about propolis and olive leaf extract activity against S. aureus vary widely among studies due to different collection sites and extraction methods [ 22 , 28 , 29 , 44 , 48 , 83 ].…”
Section: Discussioncontrasting
confidence: 67%
“…PVA/AgNPs-SM nanofiber samples with standard dimensions (1 cm × 1 cm) were added to Pseudomonas aeruginosa suspension (10 2 CFU/mL). After 24 h of incubation, the nanofibers were collected and examined under an electron microscope [ 24 ].…”
Section: Methodsmentioning
confidence: 99%